2017
DOI: 10.1080/14680629.2017.1407818
|View full text |Cite
|
Sign up to set email alerts
|

Experimental application of waste glass powder filler in recycled dense-graded asphalt mixtures

Abstract: This paper presents laboratory study results, including both bituminous mastics and mixtures tests, to assess the use of glass powder (GP) as possible surrogate to limestone filler in recycled dense-graded asphalt mixtures. To achieve a comprehensive approach, the analysis has been divided into three parts including filler, mastics and mixture characterisation. The GP has been completely studied with chemical and physical tests to compare the fundamental characteristics to the commonly used limestone filler. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 18 publications
(19 reference statements)
0
20
0
1
Order By: Relevance
“…Thus, attention has been focused on the possibility of using asphalt binder as an innovative waste treatment method [20,21,22]. Specifically, previous studies have demonstrated the feasibility of recycling various types of waste materials into asphalt materials, for instance, end-of-life vehicle tires [23], waste plastic [2,24], electronic waste powders [17], marble waste [25], waste bleaching clays [26], waste glass powder [27], waste wood resources [28], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attention has been focused on the possibility of using asphalt binder as an innovative waste treatment method [20,21,22]. Specifically, previous studies have demonstrated the feasibility of recycling various types of waste materials into asphalt materials, for instance, end-of-life vehicle tires [23], waste plastic [2,24], electronic waste powders [17], marble waste [25], waste bleaching clays [26], waste glass powder [27], waste wood resources [28], etc.…”
Section: Introductionmentioning
confidence: 99%
“…There was a general trend among the samples with GRP-WP that as GRP-WP content increases, VMA and Va results increase but VFA results decrease. Higher Va results with increasing GRP-WP content might be due to the lower level of adsorption and chemical exchange between silica and asphalt, causing more free binder in the mixtures [ 55 ]. In other words, as found by some other studies [ 4 ], GRP-WP has lower porosity compared to LS.…”
Section: Discussionmentioning
confidence: 99%
“…Lower porosity of GRP-WP causes lower absorbance of bitumen in the mixture, leading to more free binder in the mixtures. Therefore, as GRP-WP filler content increases, the amount of free binder in the mixture increases, causing the higher level of Va of the mixes [ 4 , 55 ]. In order to solve this issue, an optimum asphalt binder content could be determined for each GRP-WP filler content to avoid excessive Va.…”
Section: Discussionmentioning
confidence: 99%
“…In this study traditional limestone aggregates were used for the mix production. The limestone material is the product of limestone crushing [9] and it is configured as a different size aggregate white in colour and characterized by an amorphous structure. The limestone aggregates have been selected because it is one of the most suitable materials for the HMA production for a base layer in Italy.…”
Section: Aggregatesmentioning
confidence: 99%